Energy-efficient cooking systems, food preparation facilities, and human diets - Newborough, Marcus (Cranfield University, 1987)
This thesis aims at identifying the opportunities for saving energy, which are available to those working within the final link of the UK food system (i. e. at, or in relation to, the points of consumption). Substantial prospective savings exist, because relatively little attention has, as yet, been given to energy-thrift in food-preparation facilities. Within the food-service industry, cooking systems are characterised by high thermal capacities, excessive external surface temperatures and poorly-designed control systems. Catering staff, who use such appliances, are rarely trained to use energy wisely when preparing foods, and kitchens (and their associated dining facilities) tend to be designed without sufficient regard to energy-thrift. Similar problems prevail in domestic kitchens, but to a lesser extent because the cooks there usually pay (or contribute towards) the fuel bills. However, manufacturers still provide household appliances, which are unnecessarily energy-profligate. Furthermore most people have insufficient knowledge of the nutritional suitabilities and the primary-energy costs of their diets. Thus a major educational need exists, which must be satisfied if industrialised food systems are to become more energy efficient. This thesis attempts to make a contribution to this requirement, by analysing cooking systems, food-preparation facilities, kitchen operatives, and human diets from an energy-thrift perspective. Long-term savings (i. e. those achieved as a result of implementing the recommendations within a 15-year period) of approximately £1O p. a. (at 1987 prices) are predicted, although this could be increased substantially if Britons adopt more energy-efficient, yet nutritionally-balanced, diets.